: MIN-HEAP BASED ENERGY EFFICIENT LOAD BALANCED CLUSTERING TECHNIQUE FOR WIRELESS SENSOR NETWORK (International Journal of Engineering and Computer Science, 2017)
Clustering is one of the key mechanisms for load balancing. Clustering Algorithm is an efficient technique to improve life time and scalability of a Wireless Sensor Network. In this paper, an Energy Efficient Load Balanced Clustering Technique is proposed which is used to find energy efficiency as well as load balancing. Energy Efficient Load Balanced Clustering Technique is a min heap based Clustering algorithm. Efficiency of WSNs is measured by the total distance between nodes to the base station and data amount that has been transferred. Cluster–Head which is totally responsible for the creating cluster and cluster nodes may affect the performance of the cluster. The result show that the proposed algorithm is efficient in terms of load balancing, energy efficiency, and the number of sensor nodes that die during the network period.